Historical blocking: RU 2023-12-29 to 2023-12-31 (Russia) - Voidly (Voidly Global Censorship Index, 2023)
CRITICAL severity censorship detected in Russia. Data sourced from ooni-historical-backfill.
Censorship Incident ID: RU-2023-0009. Severity: critical. Confidence: 97%